Report on the 1st conference on adapted judo. Beyond the limits: exploring adapted judo - Maussier, Nicole; Morales, José; Magnanini, Angela; Sbriccoli, Paola; Manno, Renato; Cioni, Lorenzo; Pierantozzi, Emanuela (Revista de Artes Marciales Asiáticas, 2024)
This report explains the main contributions of the 1st conference on adapted judo, entitled “Beyond the limits: exploring adapted judo”, organized by the Italian Federation of Judo, Wrestling, Karate and Martial Arts (FIJLKAM) on April 8-9, 2024 at the FIJLKAM Olympic Center in Rome in collaboration with the European Judo Union (EJU) and the University of Rome “Foro Italico”. The various presentations highlighted the mechanisms of brain physiology that affect Autism Spectrum Disorder (ASD) and the benefits that the practice of martial arts brings to the quality of life of people with ASD and intellectual disabilities. Another block of presentations focused on the rise of adapted judo competitions and its regulation at the level of regulation and the establishment of categories of competition following a criterion of functionality to include the maximum number of people. Finally, it ended with the practical applications of adapted judo on the tatami.